Construction materials management for waste reduction in Costa Rica: barriers and motivations - Abarca-Guerrero, Lilliana (2019)
Low- and middle-income countries lag behind in research related to the construction industry and the waste problems that the sector is facing. Literature shows that waste reduction and recycling have received a continuous interest from researchers, but mainly from developed countries. Few reports from low- and middle-income countries are concerned about the reuse of masonry, concrete, and mortar in clay based building ceramics or recycling construction waste, but mostly in relation to concrete aggregates. Furthermore, few authors have described the major barriers and motivations for construction waste reduction. The objective of this paper is to report the findings on a research performed in Costa Rica with the objective to determine the barriers and motivations that the construction sector is facing to improve the management of the construction materials. The study is based on data collected in two phases. During the first phase, a survey was sent via e-mail to 419 main contractors registered at the School Federation of Engineers and Architects (CFIA). The second phase consisted of a focus group discussion with 49 professionals from the construction industry to analyse and validate the findings from the survey. Descriptive statistic methods helped to draw the conclusions. The result of the research is a comprehensive list of observed barriers and motivations for waste reduction practices in the construction sector. These are not only applicable to Costa Rica, but can be used as a guide for similar studies in other low- and middle-income countries.